Seasonal abundance and breeding biology of the Velvet Scoter Melanitta fusca at Lake Tabatskuri, Georgia - Paposhvili, Nika (Wildfowl, 2021)
Velvet Scoters Melanitta fusca from the disjunct Turkey, Georgia and Armenia nesting population were studied during 2017–2020 at what is now their last known breeding site, at Tabatskuri Lake in southern Georgia. Paired birds returned to the lake soon after thaw in April and females and young remained into November in some years. Early failing females and most males migrate to moult elsewhere in late July, although 11–19 males remained to moult on the lake each year, departing in late September/ early October. Annual summer maxima ranged from 77–92 individuals, typically comprised of 43–55% females during April–August (although inevitably fewer during incubation). Nests were totally confined to one island, where the number of breeding pairs recorded ranged from 23–33 (in 2018 and 2019, respectively). Nest success (at least one duckling hatched) varied from 74% (in 2018 and 2020) to 52% (2019), recorded for 23 (2018), 33 (2019) and 31 nests (2020), although more females were present early in the season in each year. Camera traps monitoring 11 nests recorded egg predation by Marsh Harriers Circus aerginosus on two occasions. Hatching success for all eggs laid was 54% (in 2018), 36% (2019) and 49% (2020), with overall survival of the eggs to fledging ranging from 2% (in 2018 and 2019) to 13% (in 2020). Duckling mortality was likely due to predation by Armenian Gulls Larus armenicus soon after hatching and to drowning in fishing nets. Local community engagement has stopped egg collecting on the island and contributed to reduced fishing disturbance for Velvet Scoters in the ducklings’ nursery areas, when newly-hatched young are most vulnerable to gull predation. Additionally, gull numbers were lower in 2020, which also likely contributed to the improved breeding success in that year. We urge continued vigilance and further research to confirm the direct causes of the Velvet Scoters’ poor breeding success at the site, to improve the conservation status of the species in the region.